Camarillo Certified Farmers Market Patron Survey Report: A service-learning research project conducted by CSUCI Sociology capstone students for Camarillo Hospice - Griffin, Sara; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
Research was conducted as a service-learning project by Sociology students from California State University, Channel Islands, for the benefit of Camarillo Hospice (which sponsors the Camarillo Certified Farmers Market). Analyses are based on a sample of 162 market patrons completing questionnaires during the first two weekends in March. Findings include data regarding patron demographics; patterns of patronage; satisfactions and preferences; and patrons’ awareness regarding Camarillo Hospice.